Study protocol: HepaT1ca – an observational clinical cohort study to quantify liver health in surgical candidates for liver malignancies - Damian J. Mole (BMC Cancer, 2018)
Abstract Background Accurate assessment of liver health prior to undertaking resectional liver surgery or chemoembolisation for primary and secondary cancers is essential for patient safety and optimal outcomes. LiverMultiScan™, an MRI-based technology, non-invasively quantifies hepatic fibroinflammatory disease, steatosis and iron content. We hypothesise that LiverMultiScan™can quantify liver health prior to surgery and inform the risk assessment for patients considering liver surgery or chemoembolization and seek to evaluate this technology in an operational environment. Methods/Design HepaT1ca is an observational cohort study in two tertiary-referral liver surgery centres in the United Kingdom. The primary outcome is correlation between the pre-operative liver health assessment score (Hepatica score - calculated by weighting future remnant liver volume by liver inflammation and fibrosis (LIF) score) and the post-operative liver function composite integer-based risk (Hyder-Pawlik) score. With ethical approval and fully-informed consent, individuals considering liver surgery for primary or secondary cancer will undergo clinical assessment, blood sampling, and LiverMultiScan™multiparametric MRI before and after surgical liver resection or TACE. In nested cohorts of individuals undergoing chemotherapy prior to surgery, or those undergoing portal vein embolization (PVE) as an adjunct to surgery, an additional testing session prior to commencement of treatment will occur. Tissue will be examined histologically and by immunohistochemistry. Pre-operative liver health assessment scores and the post-operative risk scores will be correlated to define the ability of LiverMultiScan™to predict the risk of post-operative morbidity and mortality. Because technology performance in this setting is unknown, a pragmatic sample size will be used. For the primary outcome, n = 200 for the main cohort will allow detection of a minimum correlation coefficient of 0.2 with 5% significance and power of 80%. Discussion This study will refine the technology and clinical application of multiparametric MRI (including LiverMultiScan™), to quantify pre-existing liver health and predict post-intervention outcomes following liver resection. If successful, this study will advance the technology and support the use of multiparametric MRI as part of an enhanced pre-operative assessment to improve patient safety and to personalise operative risk assessment of liver surgery/non-surgical intervention. Trial registration This study is registered on ClinicalTrials.gov Identifier: NCT03213314.